LOCUS STANDI IN IUDICIO – THE RIGHT OF A PARENT TO CLAIM MAINTENANCE ON BEHALF OF AN ADULT DEPENDENT CHILD Z v Z 2022 (5) SA 451 (SCA) - Razaana Denson; Glynis van der Walt (Obiter, 2024)
This matter dealt with an appeal to the Supreme Court of Appeal (SCA) from the Eastern Cape Local Division of the High Court in respect of a claim for maintenance by one parent on behalf of the adult dependent children against the other parent. The facts of the case were as follows. Mrs Z (the mother) and Mr Z (the father) were married on 10 January 1995. Two children were born of the marriage. The marriage deteriorated and Mr and Mrs Z separated for a period. Both parents continued to support their children financially. Mr Z had been maintaining the children by depositing amounts directly into their individual bank accounts. The marriage relationship between mother and father deteriorated, resulting in Mrs Z initiating divorce proceedings and claiming from Mr Z, inter alia, maintenance for herself and the two major and financially dependent children. Although they were majors, in that they were both over the age of 18, the children were financially dependent on their parents at the time of the divorce. The daughter (B) was a student and unemployed. As part of her studies, she was required to do practical training and received remuneration from time to time for the work she did for a social media company. Notwithstanding these efforts to maintain herself, B remained financially dependent on her parents. Insofar as the adult dependent son (R) was concerned, he was mobile only by means of an electric wheelchair owing to injuries sustained in a motor car accident. Despite obtaining a probationary internship in January 2021, R was still financially dependent on his parents. Owing to his injuries, it was uncertain whether he would be able to continue working as the work required long hours of sitting which caused him to suffer pressure sores, making prolonged sitting impossible.In defending the action, Mr Z raised a special plea, claiming that Mrs Z could not lodge a claim for maintenance on behalf of the children born of the marriage, since they were both adults and, therefore, had the necessary capacity to claim maintenance on their own behalf (Z v Z par 2). As a result, Mr Z contended that Mrs Z lacked the locus standi in iudicio to initiate a claim on behalf of the major children.